A Multimodal Study of Selected Campaign Posters of All Progressives Congress's Presidential Candidate in Nigeria 2023 General Elections - Davidson M. Omole; Ugoala, Bibian (Informasi, 2025)
This study is a multimodal analysis of selected political campaign posters of Bola Ahmed Tinubu "” one of the presidential candidates for the 2023 General Elections in Nigeria, of the All progressives congress (APC) political party in Nigeria. The data for the study were campaign posters that were downloaded from online sources. The data were descriptively analysed using Kress & van Leeuwen's (2006) social semiotic theory of multimodal discourse analysis. Results show that the political campaign posters were consciously used by the APC presidential candidate to promote his political agenda and solicit votes from the electorate. Through these campaign posters, he is able to disseminate information of varied intents, and project his political ideology on the minds of the electorate via visual and non-visual messages inserted in the campaign posters. The visuals and written texts on the campaign posters often reflect the socio-cultural aspects of human relationship, their political inclinations and the reality of the Nigerian nation. It further revealed that semiotic-cultural and social factors have bearings on political campaign posters in Nigeria. Based on the findings, the study concludes that campaign posters are veritable tools which have the propensity to encode socio-cultural happenings, the mindset, and intention of politicians.